2013
DOI: 10.4028/www.scientific.net/amr.701.234
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement the Dissolution Rate and Solubility of Poorly Soluble Drugs: Review

Abstract: The use of reduction and nucleation technologies in nanosize active pharmaceutical ingredient (API) is as an enabling to bring improved drug products to the marketplace demand as well as for improved drug delivery. nanoPharmaceutical field represents a hopeful set of pharmaceutical materials offering the prospect of better alternatives to optimize drug physical properties and biopharmaceutical issues such as solubility, stability and bioavailability in pharmaceutical development without changing the chemical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…PDI represents particle size distribution. Reduction in particle size offers a large surface area thereby improves solubility, dissolution, and bioavailability of poorly soluble drugs (28).…”
Section: Zeta Sizer Analysismentioning
confidence: 99%
“…PDI represents particle size distribution. Reduction in particle size offers a large surface area thereby improves solubility, dissolution, and bioavailability of poorly soluble drugs (28).…”
Section: Zeta Sizer Analysismentioning
confidence: 99%
“…4,6,[11][12][13][14][15] Some surveys showed that about 40% of marketed drugs and more than 80% of those under development have low aqueous solubility. [16][17][18][19] Solubility is one of the important parameters to achieve the desired concentration of the API in the systemic circulation, to reach the levels of pharmacological response. 17 Therefore, low aqueous solubility generates a great impact on the drug's bioavailability as they may require high doses of API.…”
Section: Introductionmentioning
confidence: 99%
“…17 Therefore, low aqueous solubility generates a great impact on the drug's bioavailability as they may require high doses of API. [17][18][19] Thus, discovering/investigating crystalline solid forms or controlling/designing more soluble forms with optimized pharmaceutical properties can be challenging or opportune for the pharmaceutical industry and academia. 13,20 There are many studies on synthesis and structural elucidation by X-ray diffraction of new pharmaceutical crystalline forms, especially multi-components such as salts and cocrystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is worrying sensation, which is caused by forceful diminishing of spurs or inducement, another specific definition for the pain which is being described by the international association for the study of pain [1], A hostile corporeal and sensitive familiarities associated with actual and potential damage of such type of tissues or may be defined as diminishing of such type of tissues, where as in medical science It has various outline for its definition or description [2]. In medical field pain is a complex phenomenon, which is appeared with variety of symptoms as it appeared as challenge which need to be solved [3]. Whenever we are discussing the pain management everybody want to get rid of from unpleasant sensation and everybody want to recover the damaged tissue and avoiding to have same exposure in future some time pain is recovered by removing the harmful stimuli and body is recovered whereas some time pain appears within body without identifying any noxious stimulus or without any damaging of tissues -pain is only reason for the consultation of physician in many developing counties [4], as whenever patients feels unpleasant sensation it alter the normal physiology of the patient and medically patients want to recover from distressing feelings.…”
Section: Introductionmentioning
confidence: 99%